Availability and use of number needed to treat (NNT) based decision aids for pharmaceutical interventions - Cassandra Nguyen; Mark Naunton; Jackson Thomas; Lyn Todd; John McEwen; Mary Bushell (Elsevier, 2021)
Background: The number needed to treat (NNT) is a medical statistic used to gauge the efficacy of therapeutic interventions. The versatility of this absolute effect measure has allowed its use in the formulation of many decision aids to support patients and practitioners in making informed healthcare choices. With the rising number of tools available to health professionals, this review synthesizes what is known of the current NNT-based tools which depict the efficacy of pharmaceutical interventions. Objective(s): To explore the current spectrum of NNT-based decision aids accessible to health professionals with a focus on the potential utility of these devices by pharmacist practitioners. Methods: A literature review was performed in MEDLINE, CINAHL, Web of Science, PsychINFO and Cochrane Library (CENTRAL, Cochrane Database of Systematic Reviews and the Cochrane Methodology Register) for studies published between January 1st 2000 and August 29th 2019. The language was restricted to English unless an appropriate translation existed. Studies that reported NNT-based decision aids of pharmaceutical or therapeutic interventions were included. One author performed study selection and data extraction. Results: A total of 365 records were identified, of which 19 NNT-based tools met the eligibility criteria, comprising of 8 tool databases and 11 individual decision aids. Decision aids appeared in multiple forms: databases, pictograms, graphs, interactive applications, calculators and charts. All aids were accessible online with a printer-friendly option, and very few came at a cost (e.g. requiring a subscription or access fee). The main tool innovators were the United Kingdom (UK) and United States (US), with English being the language of choice. Conclusions: Evidence that NNT-based decision aids can contribute to greater satisfaction and involvement of patients in medical decision making is limited and inconclusive. A case for the utilization of these tools by pharmacists has yet to be fully examined in the medical research. NNT tools may provide a valuable resource to upskill pharmacists in communication of research evidence.